(untitled) (Quinto Sol, 2013)
.The supplying of salt in sufficient amounts was one of the main concerns of the Town hall of Buenos Aires. This was a product of vital importance not only due to its usage in daily meals, but also because of its application in the conservation of the meat and leather. Such features, and the difficulties to obtain it, increased not only its commercial but also its strategic value. The discovery of local deposits allowed the inhabitants of Buenos Aires to supply themselves through periodic expeditions that were promoted by the authorities, which allowed them to exert a greater control on this production. Since the activity required and important manual labor and cargo capacity, it was a practice that many took advantage of to be employed and to obtain benefits with the commerce that was generated by such opportunity. This turned the expeditions to salt mines –organized by the authorities of the city- into great caravans that went into indigenous territory, involving a wide set of social actors from the countryside and the indigenous world.